PENGARUH PARTISIPASI ANGGARAN TERHADAP KINERJA MANAJERIAL: KOMITMEN TUJUAN SEBAGAI VARIABEL INTERVENING (STUDI EMPIRIS PADA RUMAH SAKIT TIPE A, B, DAN C, DI JAWA TENGAH DAN DAERAH ISTIMEWA YOGYAKARTA) - Eko Sugiyanto; Lilik Subagiyo (Benefit Jurnal Manajemen dan Bisnis, 2006)
The influence of budgetary participation to managerial performance has been examined in several accounting studies with conflicting result. The conflicting evidence may reflect the influence of other variables. This study examined the influence of budgetary participation to managerial performance through goal commitment as intervening variable. The population of this study is managers at hospital type A, B, and C in central java and DIY. The sample of this research is collected with contact person and mail survey method. From about of 400 questionnaires delivered, only 72 questionnaires returned and ready to analyze. The technique for examining hypothesis is path analysis. The result of this study showed that budgetary participation has positive effect to managerial performance. Other result that is shown in this study is that budgetary participation has positive effect to goal commitment, goal commitment has positive effect to managerial performance, and budgetary participation has positive effect to managerial performance through goal commitment as intervening variable.